LASSBio-897 Reduces Lung Injury Induced by Silica Particles in Mice: Potential Interaction with the A2A Receptor - Carvalho, Vinicius F.; Ferreira, Tatiana P. T.; de Arantes, Ana C. S.; Noël, François; Tesch, Roberta; Sant’Anna, Carlos M. R.; Barreiro, Eliezer J. L.; Fraga, Carlos A. M.; Rodrigues e Silva, Patrícia M.; Martins, Marco A. (Frontiers in Pharmacology, 2017)
Silicosis is a lethal fibro-granulomatous pulmonary disease highly prevalent in developing countries, for which no proper therapy is available. Among a small series of N-acylhydrazones, the safrole-derived compound LASSBio-897 (3-thienylidene-3, 4-methylenedioxybenzoylhydrazide) raised interest due to its ability to bind to the adenosine A2A receptor. Here, we evaluated the anti-inflammatory and anti-fibrotic potential of LASSBio-897, exploring translation to a mouse model of silicosis and the A2A receptor as a site of action. Pulmonary mechanics, inflammatory and fibrotic changes were assessed 28 days after intranasal instillation of silica particles in Swiss-Webster mice. Glosensor cAMP HEK293G cells, CHO cells stably expressing human adenosine receptors and ligand binding assay were used to evaluate the pharmacological properties of LASSBio-897 in vitro. Molecular docking studies of LASSBio-897 were performed using the genetic algorithm software GOLD 5.2. We found that the interventional treatment with the A2A receptor agonist CGS 21680 reversed silica particle-induced airway hyper-reactivity as revealed by increased responses of airway resistance and lung elastance following aerolized methacholine. LASSBio-897 (2 and 5 mg/kg, oral) similarly reversed pivotal lung pathological features of silicosis in this model, reducing levels of airway resistance and lung elastance, granuloma formation and collagen deposition. In competition assays, LASSBio-897 decreased the binding of the selective A2A receptor agonist [3H]-CGS21680 (IC50= 9.3 µM). LASSBio-897 (50 µM) induced modest cAMP production in HEK293G cells, but it clearly synergized the cAMP production by adenosine in a mechanism sensitive to the A2A antagonist SCH 58261. This synergism was also seen in CHO cells expressing the A2A, but not those expressing A2B, A1 or A3 receptors. Based on the evidence that LASSBio-897 binds to A2A receptor, molecular docking studies were performed using the A2A receptor crystal structure and revealed possible binding modes of LASSBio-897 at the orthosteric and allosteric sites. These findings highlight LASSBio-897 as a lead compound in drug development for silicosis, emphasizing the role of the A2A receptor as its putative site of action.